Enhancing the Refractive Index of Polymers with a Plant‐Based Pigment. Issue 44 (23rd September 2021) - Yasir, Mohammad; Sai, Tianqi; Sicher, Alba; Scheffold, Frank; Steiner, Ullrich; Wilts, Bodo D.; Dufresne, Eric R.
Abstract: Polymers are essential components of many nanostructured materials. However, the refractive indices of common polymers fall in a relatively narrow range between 1.4 and 1.6. Here, it is demonstrated that loading commercially‐available polymers with large concentrations of a plant‐based pigment can effectively enhance their refractive index. For polystyrene (PS) loaded with 67 w/w% β‐carotene (BC), a peak value of 2.2 near the absorption edge at 531 nm is achieved, while maintaining values above 1.75 across longer wavelengths of the visible spectrum. Despite high pigment loadings, this blend maintains the thermoforming ability of PS, and BC remains molecularly dispersed. Similar results are demonstrated for the plant‐derived polymer ethyl cellulose (EC). Since the refractive index enhancement is intimately connected to the introduction of strong absorption, it is best suited to applications where light travels short distances through the material, such as reflectors and nanophotonic systems. Enhanced reflectance from films is experimentally demonstrated, as large as sevenfold for EC at selected wavelengths. Theoretical calculations highlight that this simple strategy can significantly increase light scattering by nanoparticles and enhance the performance of Bragg reflectors. Abstract : High refractive index materials based on commercially available polymers (polystyrene and ethyl cellulose (EC)) and plant based pigment, β‐carotene (BC) are reported. The refractive index increases linearly with increased loading of pigment in polymers. A value of refractive index as high as 2.15 is achieved at 528 nm wavelength for EC loaded with 67 w/w% BC.